Взаємодія оксидів дво- й тривалентних металів з розплавами Cs₂O−P₂O₅ - Струтинська, Н.Ю.; Затовський, І.В.; Слободяник, М.С. (Видавничий дім "Академперіодика" НАН України, 2008)
The interaction of a number of oxides (fluorides) of bi- or trivalent metals with caesium phosphate’s melts is investigated. The main trends in crystallization depending on the Cs/P ratio in a starting melt are discussed. The crystallization fields of CsMIIIP2O7 (MIII −Cr, Fe, In, Lu, Tb), MIIIPO4 (MIII −Sm, La, Bi), Cs2MII 2 P6O18 (MII −Mg, Ni), Ni2P2O7, Ni3(PO4)2, and CsZnPO4 are defined. The obtained compounds have been characterized by the powder X-ray diffraction and FTIR-spectroscopy.